Hubungan Depresi dengan Fatigue pada Pasien Hemodialisis - Sri Suparti; Siti Nurjanah (Universitas 'Aisyiyah Yogyakarta, 2018)
The purpose of this study to determine the relationship of fatigue with depression. This descriptive correlative analytic research with 78 samples. The questionnaire used was Functional Assessment of Chronic Illness Therapy-G and Zung Self-rating Depression Scale. The mean fatigue score was 24.21 and 44.50 for depression. Pearson correlation result showed r=0.646 (p0.05). Logistic regression analysis showed R=4.18%, which means depression predicted about 40% by fatigue, and 60% influenced by other variables. There is a strong relationship between fatigue and depression. Management of depression and fatigue should be standard in patient care.